The Road to Serfdom after 75 years - Bruce Caldwell (Duke University, Center for the History of Political Economy (CHOPE), 2019)
F. A. Hayek published The Road to Serfdom in 1944, so 2019 marks the 75th anniversary of the event. The paper traces how Hayek came to write the book, who his opponents were, and how the book got interpreted by both friends and critics after its publication. Because the book is more typically invoked than read, part of the goal of the paper is to identify and correct some common misperceptions.
Keywords: B2; B3; B51; B53; 330; F. A. Hayek; The Road to Serfdom; liberalism; socialism; conservatism; German Historical School; laissez faire; J. M. Keynes